Antioxidant action of deprotonated flavonoids: Thermodynamics of sequential proton-loss electron-transfer. (December 2020) - Biela, Monika; Rimarčík, Ján; Senajová, Erika; Kleinová, Andrea; Klein, Erik
Abstract: Despite the intensive research on radical scavenging action of flavonoids, a systematic study of the thermochemistry for their mono-deprotonated species in aqueous solution is still missing. In this work, reaction enthalpies related to Sequential Proton-Loss Electron-Transfer (SPLET) mechanism were theoretically investigated for all mono-deprotonated forms of nine flavonoids: apigenin, luteolin, fisetin, kaempferol, quercetin, taxifolin, tricetin, tricin and cyanidin. Differences in reaction enthalpies of the first and the second deprotonation can be lower than 10 kJ mol −1, when two successive deprotonations occur in different aromatic rings of the molecule. For neutral flavonoids, thermodynamically preferred deprotonation sites are 4′-OH and 7-OH groups. In cyanidin (cation in native form), preferred second deprotonation site is 5-OH group. In the case of the formation of the preferred dianions, reaction enthalpies of the second proton loss are not affected by the structural distinctions between the flavonoids. In aqueous solution, deprotonated flavonoids show higher tendency to enter SPLET mechanism in comparison to Hydrogen Atom Transfer (HAT) or electron transfer. Graphical abstract: Image 1 Highlights: Antioxidant action of mono-deprotonated flavonoids is studied in aqueous solution. Reaction enthalpies of sequential proton-loss electron-transfer are investigated. Thermodynamically favored double-deprotonated species are identified. Preferred mechanism of radical scavenging of deprotonated flavonoids is determined.